Effective Strategies in Learning Islamic Cultural History for Cultivating Moral Values - Masnawati, Eli; Yuliastutik, Yuliastutik; Khotimah, Anik Khusnul; Yuliah, Yuliah; Aliyah, Nelud Darajaatul (Metromedia, 2022)
Islamic Cultural History (IHR) has a strategic role in shaping students' morals through instilling moral values rooted in Islamic teachings. This study aims to explore the role of IHR teachers in shaping students' morals and identify effective learning methods and strategies to support this goal. The research method used is a literature review, which includes analyzing various theoretical sources, previous research, and best practices related to IHR learning. The results show that IHR teachers have a great responsibility as material deliverers, and as role models who reflect moral values. Effective methods in fostering student morals include exemplary, mau'idzah and advice, habituation, stories, and punishment and reward. IHR learning also integrates values such as respecting reason, demanding knowledge, avoiding blind taklid, and prohibiting damage, which are relevant to the challenges of globalization. Factors that influence the formation of student morals include the role of the family, student personality, community environment, and media influence. Effective learning strategies, such as technology integration, contextual approaches, and strengthening collaboration between teachers, parents, and communities, can increase the effectiveness of IHR learning. With the right approach, IHR learning can produce a young generation that is intellectually intelligent, and has noble morals and is ready to face the challenges of the times.